The Legal Problems of the Child Trafficking Crime in Indonesia in the View of Human Rights - Mini Setiawati; Sofyan Wimbo Agung Pradnyawan; Dimas Pramodya Dwipayana (Activa Yuris: Jurnal Hukum, 2021)
Human rights are basic rights that are inherent in every human being that cannot be reduced at all. This right can only be taken away through legitimate state institutions and with legitimate legal reasons as well, but the increasingly globalized economic flow, and an increasingly advanced social order and leads to industrialization in all fields, creating many new crime models with an increasing trend, one of them is the crime of human trafficking. They are not only adults who are vulnerable to this crime, but it turns out that children are the most vulnerable to this crime, so that their human rights are threatened in all aspects. This study uses a normative juridical method with only the study of laws and literature. The result of the research is that the laws and regulations protecting the human rights of children from human trafficking crimes are inadequate and tend not to be in sync with one another so that they have not been maximized in realizing protection for child victims of human trafficking